Network Security: Li-Fi: Data Onlight Instead of Online (International Journal of Engineering and Computer Science, 2014)
With the vast growing gadgets, their usage and their developments led to the advancement in the Wi-Fi which provides a technology so called Li-Fi.Li-Fi is a technology that makes use of LED light which helps in the transmission of data much more faster and flexible than data that can be transmitted through Wi-Fi. Light reaches nearly everywhere so communication can also go along with light freely. Light Fidelity is a branch of optical wireless communication which is an emerging technology. By using visible light as transmission medium, Li-Fi provides wireless indoor communication. The bit rate achieved by Li-Fi cannot be achieved by Wi-Fi.. Dr herald Haas the professor of mobile communications at the university of Edinburgh school of engineering ,first time publically displayed the proof of Light Fidelity (Li-Fi) ,a method of Visible Light communication(VLC). Li-Fi is the transfer of data through light by taking fiber out of fiber optics and sending data through LED light.He envisions a future where data for laptops, smart phones, and tablets is transmitted through the light in a room. And security would be snap – if you can’t see the light, you can’t access the data.